Safeguarding, child protection and abuse in sport international perspectives in research, policy and practice - Lang, Melanie; Hartill, Mike (London Routledge, Taylor & Francis, 2016)
"The safeguarding of children and young people participating in sport has become an increasingly prominent concern in policy-making and research communities around the world. Major organisations such as the IOC and UNICEF now officially recognize that children in sport can be at risk of exploitation and abuse, and this concern has led to the emergence of new initiatives and policies aimed at protecting vulnerable young people and athletes. This book is the first to comprehensively review contemporary developments in child protection and safeguarding in sport on a global level. The book is divided into two parts. Part One critically analyses current child protection and safeguarding policy and practice in sport across a range of countries, including the US, Canada, the UK, Australia, China and Germany, providing a global context for current policy and practice. This represents the most comprehensive review to date of the landscape of child protection and safeguarding in sport and provides a starting point for critical international comparisons. Part Two explores a range of issues related to child protection and safeguarding in sport, including many not covered in previous books, such as emotional abuse, injury and over-training. While in many instances the impetus for policy in this area has arisen from concerns about sexual abuse, the second part of this book therefore opens up a broader, more holistic approach to child and athlete welfare. By bringing together many of the leading researchers working in child and athlete protection in sport from around the world, this book is important reading for all advanced students, researchers, policy-makers or practitioners working in youth sport, physical education, sports coaching, coach education or child protection"--Provided by publisher.
Machine generated contents note: pt. I Global perspectives -- 1. Safeguarding and child protection in sport in England / Mike Hartill -- 2. Safeguarding children and young people in Danish sport / Jan Toftegaard-Støckel -- 3. Preventing child maltreatment and transgressive behaviour in Flemish sport / Kristine De Martelaer -- 4. (Sexual) intimidation in sport in the Netherlands / Lieke Vloet -- 5. Child protection in German sport / Bettina Rulofs -- 6. Safeguarding and child protection in sport in two Southern European countries: Greece and the Republic of Cyprus / Maria Papaefstathiou -- 7. Child protection and welfare in Spanish sport / Montserrat Martin -- 8. Safeguarding children from violence and abuse in Slovenian sport / Melanie Lang -- 9. Protecting children from abuse and exploitation in South African sports / Rudolph Leon Van Niekerk -- 10. Athlete welfare and protection policy development in the USA / Connee Zotos -- 11. Athlete welfare and safeguarding in sport in Canada / Sylvie Parent -- 12. Child safety and wellbeing in Australian sport / Kate Russell -- 13. The protection of young athletes in China: policy and practice / Zhang Ling -- 14. Who safeguards the child in Japanese sports? / Atsushi Nakazawa -- pt. II Developing fields of enquiry -- 15. Safeguarding athletes from emotional abuse / Gretchen Kerr -- 16. Safeguarding the welfare of disabled people in sport: some policy issues and considerations / Andy Smith -- 17. Physical training as a potential form of abuse / Rhodri S. Lloyd -- 18. Safeguarding, injuries and athlete choice / Andrea Scott -- 19. Evaluation in safeguarding and child protection in sport / Jimmy O'Gorman.
Originally published in 2015.
First issued in paperback 2016.
Keywords: Sports for children -- Safety measures; Sports for children -- Moral and ethical aspects; Sports for children -- Research; Sports for children -- Cross-cultural studies; Child welfare -- Cross-cultural studies; Child abuse -- Cross-cultural studies; Child sexual abuse -- Cross-cultural studies; Abused children -- Services for -- Cross-cultural studies; Child abuse -- Prevention -- Cross-cultural studies; Child sexual abuse -- Prevention -- Cross-cultural studies